Sociotechnical Aspects of Lean and Sustainability - Azyyati Anuar; Rohaizah Saad; Rushami Zein Yusoff; Daing Maruak Sadek (International Journal of Supply Chain Management, 2019)
In recent years, lean healthcare has been used by numerous scholars as a major trend for exploring the purpose of practicing lean healthcare in an operational context but apparently not considering the human or social factors. Furthermore, less studies have been conducted on how social or sociotechnical aspects of lean enables the achievement of sustainability in healthcare organizations, which also includes the three main pillars, namely economic, social, and environmental aspect. Therefore, this paper intended to examine the link between sociotechnical aspects of lean and sustainability in the healthcare sector. It also discussed theoretical approaches that explain these variables, namely Sociotechnical and Stakeholder theories. Finally, this paper has given important significance for academic researchers who intend to study the sociotechnical aspects of lean and sustainability as well as practitioners who deal with complex problems. Conclusions and future works are also included in this paper.